Microbacterium telephonicum sp nov., isolated from the screen of a cellular phone - Rahi, Praveen; Kurli, Rashmi; Pansare, Aabeejjeet N.; Khairnar, Mitesh; Jagtap, Shubhangi; Patel, Nisha B.; Dastager, Syed G.; Lawson, Paul A.; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2018)
A cultivation-based study of the microbial diversity of cellular phone screens led to the isolation of a Gram-stain-positive, aerobic, rod-shaped and non-endospore-forming bacterium, designated S2T63(T), exhibiting phenotypic and genotypic characteristics unique to the type strains of closely related species. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the strain is a member of Microbacterium, and most closely related to Microbacterium aurantiacum IFO 15234(T) and Microbacterium kitamiense Kitami C2(T). The DNA-DNA relatedness values of the strain S2T63(T) to M. aurantiacum KACC 20510(T), M. kitamiense KACC 20514(T) and Microbacterium laevaniformans KACC 14463(T) were 65% (+/- 4), 29.5% (+/- 3) and 55.9% (+/- 4), respectively. The genomic DNA G+C content was 71.8 mol%. The major fatty acids were anteiso C-15:0, iso-C-16 : 0, C-16 : 0 and anteiso-C-17 : 0. The main polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and two unidentified polar lipids. The peptidoglycan contained the amino acids glycine, lysine, alanine and glutamic acid, with substantial amounts of hydroxy glutamic acid detected, which is characteristic of peptidoglycan type B1 alpha. The predominant menaquinones were MK-12 and MK-13. Rhamnose, fucose and galactose were the whole-cell sugars detected. The strain also showed biofilm production, estimated by using crystal violet assay. Based on the results of the phenotypic and genotypic characterizations, it was concluded that the new strain represents a novel species of the genus Microbacterium, for which the name Microbacterium telephonicum is proposed, with S2T63(T) (=MCC 2967 T = KACC 18715 T = LMG 29293(T)) as the type strain.
Keywords: actinobacteria; bio-film; MALDI-TOF MS; mobile phone

Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Microbacterium enclense sp. nov., isolated from sediment sample (vol 65, pg 2064, 2015) - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed G. (International Journal of Systematic and Evolutionary Microbiology, 2019)

Molecular networking and whole-genome analysis aid discovery of an angucycline that inactivates mTORC1/C2 and induces programmed cell death - Dan, Vipin Mohan; Vinodh, J. S.; Sandesh, C. J.; Sanawar, Rahul; Lekshmi, Asha; Kumar, R. Ajay; Kumar, T. R. Santhosh; Marelli, Uday Kiran; Dastager, Syed G.; Pillai, M. Radhakrishna (ACS Chemical Biology, 2020)
Rediscovery of known compounds and time consumed in identification, especially high molecular weight compounds with complex structure, have let down interest in drug discovery. In this study, whole-genome analysis of microbe and Global Natural Products Social (GNPS) molecular networking helped in initial understanding of possible compounds produced by the microbe. Genome data revealed 10 biosythethic gene clusters that encode for secondary metabolites with anticancer potential. NMR analysis of the pure compound revealed the presence of a four-ringed benz[a]anthracene, thus confirming angucycline; molecular networking further confirmed production of this class of compounds. The type II polyketide synthase gene identified in the microbial genome was matched with the urdamycin duster by BLAST analysis. This information led to ease in identification of urdamycin E and a novel natural derivative, urdamycin V, purified from Streptomyces sp. OA293. Urdamycin E (Urd E) induced apoptosis and autophagy in cancer cell lines. Urd E exerted anticancer action through inactivation of the mTOR complex by preventing phosphorylation at Ser 2448 and Ser 2481 of mTORC1 and mTORC2, respectively. Significant reduction in phosphorylation of the major downstream regulators of both mTORC1 (p70s6k and 4e-bp1) and mTORC2 (Akt) were observed, thus further confirming complete inhibition of the mTOR pathway. Urd E presents itself as a novel mTOR inhibitor that employs a novel mechanism in mTOR pathway inhibition.

Molecular insights of fungal endophyte co-inoculation with Trichoderma viride for the augmentation of forskolin biosynthesis in Coleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Babu, C. S. Vivek (Phytochemistry, 2021)
To understand the compatibility of three native endophytic fungi Phialemoniopsis cornearis (SF1), Macrophomina pseudophaseolina (SF2) and Fusarium redolens (RF1) with Trichoderma viride (TV1) on Coleus forskohlii in enhancing plant growth and forskolin content, field experiments were conducted. Co-inoculation of RF1+TV1 showed significant improvement in plant growth (52%), root biomass (67%), and in planter forskolin content (94%), followed by treatment with SF2+TV1 and SF1+TV1. qRT-PCR was carried out to quantify expression of five key forskolin biosynthetic pathway genes (CfTPS2, CfTPS3, CfTPS4, CfCYP76AH15, and CfACT1-8) in RF1+TV1 treated C. forskohlii plants. Elevated expression of CfTPS2, CfTPS4, CfCYP76AH15 and CfACT1-8 genes was observed with RF1+TV1 combination as compared to uninoculated C. forskohlii plants. Besides, RF1+TV1 treatment considerably reduced the severity of nematode infection of C. forskohlii plants under field conditions. Thus, congruent properties of F. redolens (RF1) were witnessed with co-inoculation of T. viride (TV1) under field conditions which resulted in enhanced forskolin content, root biomass, and reduced nematode infections in C. forskohlii. Overall, this approach could be an economical and sustainable step towards cultivation of commercially important medicinal plants.
Keywords: Co-inoculation; Coleus forskohlii; endophytes; Forskolin; Lamiaceae; Trichoderma viride

Multifunctional metabolites of Streptomyces kunmingensis BS19 from bamboo rhizosphere soil - Sangeetha, Murthy; Sasirekha, Sivakumar; Mahendran, Jaganathan; Sivarajan, Anbalmani; Radhakrishnan, Manikkam; Manigundan, Kaari; Dastager, Syed G.; Sengottuvelu, Singaravel; Balagurunathan, Ramasamy (International Microbiology, 2024)
A pigmented bioactive molecule from Streptomyces kunmingensis BS19 was isolated, characterized, and evaluated for anti-infective, antiproliferative, and wound-healing properties. The yellow–red pigment produced from the strain BS19 showed promising activity against methicillin-resistant Staphylococcus aureus (MRSA) and Mycobacterium tuberculosis. Extracellular bioactive pigment from the strain BS19 was produced by agar surface fermentation and purified through bioassay guided preparative HPLC-based purification. Based on the results of UV, FT-IR, GC–MS, 1H NMR, and 13C NMR spectral analyses, the purified pigment was identified as a chromopeptide class of molecule with phenoxazinone chromophore. Its molecular weight was determined as the chemical formula C64H90N12O16 and molecular weight 1283 g/mol. It exhibited promising antimicrobial activity against Staphylococcus aureus (ATCC 1720) and antiproliferative activity against 14 types of human cancer cell lines. It showed good in vivo wound-healing activity in the rat model. The present study explored Streptomyces kunmingensis as a newly added source for the isolation of chromopeptide antibiotics for antimicrobial, wound-healing, and anticancer applications.